TARI BEGALAN DI TENGAH PERUBAHAN SOSIAL MASYARAKAT BANYUMAS. - Karyono Karyono (Greget, 2009)
The Begalan tradition perfotming art Banyumas is sprit of life cultural Banyumas peole. Begalan is communal performing art in Banumas cultural not haven use people life in Gotong Royong. Begalan in people spirit to be change social process, because this Begalan develop changing is fungtional social cultural Keyword : Begalan, social change